Outbreak of infections due to kpc-2-producing klebsiella pneumoniae in a hospital in Crete (Greece) - Maltezou, Helena C.; Giakkoupi, Panagiota; Maragos, Antonios; Bolikas, M.; Raftopoulos, Vasilios; Papahatzaki, H.; Vrouhos, G.; Liakou, Vassiliki; Vatopoulos, Alkiviadis C. (My University, 2009)
Starting in May 2007, an ongoing outbreak of infections due to carbapenem resistant KPC-2-producing Klebsiella pneumoniae occurred in a tertiary care hospital in Crete (Greece). The outbreak involved 22 patients, none of whom had travelled in a country with known high prevalence of such isolates. KPC-producing K. pneumoniae strains were mainly isolated from patients admitted in the Intensive Care Unit, on mechanical ventilation, with prolonged hospitalization, prolonged administration of antibiotics, and prolonged administration of carbapenems. Clinical diagnoses were: pneumonia (62% of cases), surgical site infection (19%), bacteremia (9.5%), urinary tract infection (4.7%), and peritonitis (4.7%). Overall, 61 KPC-producing K. pneumoniae isolates were recovered, mainly from the respiratory tract (59.1%), catheter tip (22.7%), surgical site (18.2%), and blood (18.2%). Among 16 patients for whom therapeutic data were available, 14 (87.5%) were treated with a combination of colistin and/or tigecycline and/or garamycin. Clinical failure was noted in 22.2% of 18 patients available for assessment of clinical outcome, and microbiologic failure in 87.5% of 8 patients available for assessment of microbiologic outcome. In conclusion, an outbreak of KPC-producing K. pneumoniae infections has occurred in a tertiary care hospital in Greece, with significant associated morbidity and mortality. Prospective studies are required to evaluate the available therapeutic options for these infections. Our efforts should focus on rational use of available antibiotics, enhancement of infection control measures, and implementation of active antibiotic resistance surveillance.
Keywords: KPC; Carbapenemase; Resistance; Nosocomial outbreak; Klebsiella pneumoniae; Tigecycline; Colistin